An Acute, Double‐Blind, Placebo‐Controlled Crossover Study of 320 mg and 640 mg Doses of a Special Extract of Bacopa monnieri (CDRI 08) on Sustained Cognitive Performance. (19th December 2012) - Downey, Luke A.; Kean, James; Nemeh, Fiona; Lau, Angela; Poll, Alex; Gregory, Rebecca; Murray, Margaret; Rourke, Johanna; Patak, Brigit; Pase, Matthew P.; Zangara, Andrea; Lomas, Justine; et al.
Abstract : Standardized extracts of the traditional Ayurvedic medicine Bacopa monnieri (BM) (Brahmi) have been recently shown to have cognitive enhancing effects in chronic administration studies. Pre‐clinical work has also identified a number of acute anxiolytic, nootropic, and cardiovascular effects of BM. There has, however, been little research on the acute effects of BM on cognitive function. The current study aimed to assess the acute effects of a specific extract of BM (KeenMind® ‐ CDRI 08) in a double‐blind, placebo‐controlled study in normal healthy participants who completed a cognitively demanding series of tests. Twenty‐four healthy volunteers completed six repetitions of the Cognitive Demand Battery (CDB) after consuming a placebo, 320 mg BM or 640 mg of BM in a cross‐over design and provided cardiovascular and mood assessments before and after treatment. Change from baseline scores indicated that the 320 mg dose of BM improved performance at the first, second, and fourth repetition post‐dosing on the CDB, and the treatments had no effect upon cardiovascular activity or in attenuating task‐induced ratings of stress and fatigue. It was concluded that assessment of an earlier pharmacological window and use of less memory‐specific cognitive tests together with more temporally sensitive measures of brain activity may improve our understanding of the acute neurocognitive properties of BM. Copyright © 2012 John Wiley & Sons, Ltd.